Foreign policy benchmarks of Pavlo Skoropadskyi's government (according to archival and autobiographical materials) - Bogdan Levyk (Cхід, 2017)
The author reviews some archival documents and materials of Pavlo P. Skoropadskyi, Hetman of the Ukrainian state, his personal memoirs and executive decisions on foreign policy issues over a period of April-December 1918. Pavlo Skoropadskyi's stand as to building the state and his commitment to the pro-Russian vector are demonstrated. Some examples of practical steps taken by Pavlo Skoropadskyi's government to gain understanding with the Entente countries after Germany and Austria-Hungary lost the war are given. Based on its organizational structure, the type of the Hetman state is defined. An example of rapport with new temporary state formations on the Don and Kuban Rivers is given. The paper describes radical and prompt actions of the Hetman government, taken to draw the Crimea under the dominion of Ukraine. The fallacy of the pro-Russian line of policy of Hetman P. Skoropadskyi in the context of the German and Austro-Hungarian occupation is pointed out. The ambiguous course of Ukraine is exemplified by the formation of its Armed Forces, Cabinet of Ministers and delaying in the implementation of the agrarian reform. The attitude of Pavlo Skoropadskyi to the Ukrainians and the Galicians is demonstrated through specific references to his statements. The paper shows some practical steps in opening embassy missions and consular agencies in European countries, which point to the efforts of the Cabinet of Ministers to win international recognition and authority for the Ukrainian state. A situational geopolitical change of the diplomatic relations is demonstrated by the example of Romania. The main causes of the anti-Hetman uprising are defined as the lack of a negotiation process with representatives of socialist and democratic forces of Ukraine, incapability to enlist the support of rural masses and inferior moods in respect of Russia.